THE IMPACT OF SOCIAL MEDIA ON CHANGING BEHAVIOR PATTERNS OF GENERATION Z - Mujiwati, Yuniar; Laili, Innayatul (Cebong Journal, 2023)
Internet service providers (APJII) conducted a survey on the increase and types of internet content that are often accessed by the public in 2020 which showed as many as 61% of the Indonesian population prefers to access social media than online games and the like. Excessive use of social media results in neglect of the surrounding environment. It can even commit acts outside the boundaries such as suicide due to cyberbullying. This was also felt by students at SMK Kesehatan Sakinah Pasuruan, who were affected by the influence of social media. The purpose of this study is to describe the behavior of students of SMK Kesehatan Sakinah, the influence of social media that has an impact on the behavior of students of SMK Kesehatan Sakinah, teacher strategies in overcoming shifts in generation Z behavior in students, as well as supporting factors and obstacles for teachers in overcoming the influence of social media on changes in behavior of students of SMK Kesehatan Sakinah. This research uses descriptive qualitative methods.